Asking For Money Back-Chilling Commercialization Or Recouping Public Trust In The Context Of Stem Cell Research? - Herder, Matthew (Science and Technology Law Review, 2008)
As publicly funded institutions have increasingly embraced the goal of commercializing scientific research, concerns about private appropriation have become familiar refrain. One commonly suggested remedy is to create some kind of “recoupment” provision whereby the State, on behalf of the public, receives a certain percentage of profits realized. The Bayh-Dole Act originally included a recoupment provision but it was deleted by a legislative committee. Countries around the globe attempting to emulate Bayh-Dole have, whether by design or default, reinforced the underlying logic against recoupment, which is essentially as follows: obligations to provide direct financial returns undermine the commercialization process and therefore threaten what the public cares about most, i.e. the production of new goods. Despite regular controversies over alleged windfalls to industry, this logic has continued to prevail—until now. The California Institute of Regenerative Medicine (CIRM) has recently issued two intellectual property policies applicable to non-profit and for-profit grant recipients respectively, each of which contains mechanisms to recoup a portion of the public’s tax dollar investment. Why? This Article aims to explore that question by: one, further explaining the curious history in which the wisdom against recoupment came to prevail; two, probing the details of CIRM’s intellectual property policies and examining the arguments for and against the recoupment formulae they establish; and three, revealing the limits of what is actually known about whether such mechanisms exert a chilling effect on the commercialization process, and whether or not a direct financial return is what the public values most. In the end, the value of recoupment may be best conceived of in democratic terms: as one means of attempting to balance a host of conflicting views, and preserving public trust as the many promises of biotechnology become increasingly integral to nation-building strategies and our lives.